1993
DOI: 10.1002/syn.890150406
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical requirements for pseudoirreversible inhibition of opioid mu receptor binding by the 3‐methylfentanyl congeners, RTI‐46144 and its enantiomers: Evidence for different binding domains

Abstract: Fentanyl and its congeners are of interest not only because of their clinical applications, but also because certain members of this series of opioid analgesics exhibit unique properties, such as acting as pseudoirreversible inhibitors of mu receptor binding, both in vitro and in vivo. Previous studies showed that pretreatment of membranes with (+)-cis-3-methylfentanyl resulted in a lower affinity interaction of [3H]ohmefentanyl with the mu binding site, as well as an increased dissociation rate. The present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…and 6␤-125 iodo-3,14-dihydroxy-17-cyclopropylmethyl-4,5␣-epoxymorphinan ([125I]IOXY) as described elsewhere (Ni et al, 1993. In some experiments (Fig.…”
Section: Binding Assaysmentioning
confidence: 99%
“…and 6␤-125 iodo-3,14-dihydroxy-17-cyclopropylmethyl-4,5␣-epoxymorphinan ([125I]IOXY) as described elsewhere (Ni et al, 1993. In some experiments (Fig.…”
Section: Binding Assaysmentioning
confidence: 99%
“…Our data consistently showed that isomer 1c had a much lower Ki value than isomer 1a, whereas those of Wang et al (1995) showed that isomer 1a had a much lower Ki value than isomer 1c. The reanalysis showed that samples used in our binding studies in previously published work (Brine et al, 1992(Brine et al, , 1995Ni et al, 1993b) were mislabeled. The sample labeled 1a actually contained 1c, and the sample labeled 1c actually contained 1a.…”
Section: Introductionmentioning
confidence: 95%
“…The availability of the four resolved enantiomers allowed us to determine the stereochemical requirements for the pseudoirreversible binding described above as well as their in vivo actions (see below). The results (Ni et al, 1993b) showed that the (3R,4S) configuration was essential for both high affinity binding and pseudoirreversible inhibition, while the 2S configuration of the 2-OH provides additional enhancement of binding affinity and potency. Interestingly, although 1b and 1a both produced pseudoirreversible inhibition of µ receptor binding, there were in fact subtle differences between these ligands.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations